Badania nad polikondensacją 3-merkaptopropylotrietoksysilanu z tetraetoksysilanem - Wolak, Paweł (The Investigation of Polycondensation of 3-Mercaptopropyltriethoxysilane with Tetraethoxysilane, 2008)
The investigation showed that there is a considerable influence of the polycondensation reaction procedure on the properties of products obtained. Reactive products obtained at optimal conditions are soluble neither in water nor in organic solvents and thus they can be used, in their capacity, like ion- or electron-exchangers. The products were temperature-stable up to 200°C. A series of products having different functional-groups-capacity could be obtained as a function of the molar-ratio of monomers used in policondensation. To test alternative ways leading to strong acidic cationites, additional investigation was carried out, oxidizing thiolic groups to sulfonic groups. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 173-182